Microcontroller-based smart foot as an educational tool for teaching reflexology nerve points to visually impaired massage trainers and trainees - Dina Fitriana Rosyada; Krida Tri Wahyuli; Muhammad Hasani; Nur Rokhman (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2023)
The limited sense of sight makes it difficult for blind people to get a decent job. One of the jobs performed by the blind is a reflexology massager. Becoming a reflexology masseuse with visual limitations has several obstacles in learning reflexology. The purpose of this research is to make reflexology educational aids that are easily understood by blind masseurs so that blind masseurs can improve reflexology competence and determine the appropriate massage nerve points. The making of teaching aids is carried out using the Research and Development method with five stages, namely information gathering, planning, development, trials with students and coaches, and evaluation. The results of this study are a prototype in the form of a microcontroller-based smart demonstration leg called Smart Massage Tools. The output of the Smart Massage Tools prototype is sound which is suitable for use by blind people who want to study reflexology independently. Smart Massage Tools have higher time effectiveness and understanding than massage training using manual props.